Investasi dan Pertumbuhan Ekonomi Regional (Studi Kasus pada 26 Propinsi di Indonesia, Pra dan Pasca Otonomi - Jamzani Sodik; Didi Nuryadin (Economic Journal of Emerging Markets, 2005)
The aim of this study is to examine the affect of investment on regional economic growth 26 province pre and pasca authonomy for periods of 1998-2003 using GLS method (General Least Square) for process polling data. Factor that affect the regional economic growth are foreign direct investments (X1), direct domestic investmens (X2), we also identify other factors (as controlled variables) that can influence the regional economic growth. These variables are labor force (X3), inflation rate (X4), and rate openness economic pro¬vince (X5).The results found regional economic growth for periods 1998-2003 are influenced by foreign direct investments (X1), labor force (X3), and rate openness economic pro¬vince (X5). However direct domestic investments (X2), and inflation rate (X4) do not affect to regional economic growth. But for periods 1998-2000 (pre authonomy) foreign direct in¬vestments (X1), and rate openness economic province (X5) affect to regional economic growth. Periods 2000-2003 (pasca authonomy) inflation rate (X4) and rate openness eco¬nomic province (X5) affect to regional economic growth.Keywords:    investment, foreign direct investments, direct domestic investments, regional eco¬nomic growth, pre authonomy, pasca authonomy, and panel data.